2011
DOI: 10.3109/00365548.2011.585178
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus in a cohort of HIV-infected pregnant women: Prevalence of colonization, identification and antimicrobial susceptibility profile

Abstract: Group B Streptococcus (GBS) is a leading cause of infectious morbidity in newborns. We describe the prevalence of GBS colonization and the serotypes and antibiotic susceptibility profiles of isolates obtained from a cohort of human immunodeficiency virus (HIV)-infected pregnant women. This was a cross-sectional study at a centre for the prevention of mother-to-child transmission of HIV. Vaginal and rectal swabs were collected at 35-37 weeks of gestation from 158 eligible women. GBS isolates were serotyped and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
3
8
1
Order By: Relevance
“…Serotypes VI to VIII were not found, and these serotypes are still rarely reported from other locations [9]. Our results are in agreement with previous data obtained in earlier Brazilian studies with isolates obtained from the South and Southeast regions [10,15,35], as well as with data published in several other countries [24,25]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Serotypes VI to VIII were not found, and these serotypes are still rarely reported from other locations [9]. Our results are in agreement with previous data obtained in earlier Brazilian studies with isolates obtained from the South and Southeast regions [10,15,35], as well as with data published in several other countries [24,25]. …”
Section: Discussionsupporting
confidence: 93%
“…In Brazil, previous studies showed that serotypes Ia, II, III and V were found in 68.2% of isolates predominantly from vaginal specimens of asymptomatic pregnant woman [14]. On the other hand, serotype IV was detected in 13.1% of the isolates from Curitiba city, Paraná state, Brazil, being most of them from infectious cases [13], and serotypes Ib (34.9%) and Ia (25.6%) were predominant among a cohort of HIV-infected pregnant women in Rio de Janeiro city [35]. …”
Section: Discussionmentioning
confidence: 99%
“…The GBS colonization rate of 8.3% observed in the present study is lower than the rate of 20%–31% reported in previous studies of HIV‐infected pregnant women in Brazil [3,5], though the CIs for the prevalence estimates overlap between the present study and that of El Beitune et al [3]. Previous studies have shown that GBS colonization rates can vary widely among pregnant women in different settings and that the rates are not consistently higher among HIV‐infected women than their non‐infected peers [10–12].…”
Section: Discussioncontrasting
confidence: 87%
“…Rectovaginal colonization with GBS may be more frequent among HIV‐infected pregnant women than their counterparts without HIV infection; furthermore, HIV‐exposed but uninfected infants seem to be at higher risk of neonatal GBS‐related disease than infants of HIV‐negative mothers [3–6]. Little information is available, however, regarding institutional policies that aim to address prevention of neonatal GBS infection among infants of HIV‐infected pregnant women in Latin American countries.…”
Section: Introductionmentioning
confidence: 99%
“…According to Joao et al, the overall anogenital prevalence of GBS colonization was 49/158 (31.0%) in a cohort of HIV-positive pregnant women during the third trimester of pregnancy [5]. …”
Section: Resultsmentioning
confidence: 99%